2011
DOI: 10.1016/j.ajic.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of surrogate coronaviruses on hard surfaces by health care germicides

Abstract: Only ethanol reduced infectivity of the 2 coronaviruses by >3-log(10) after 1 minute. Germicides must be chosen carefully to ensure they are effective against viruses such as severe acute respiratory syndrome coronavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 28 publications
2
123
0
6
Order By: Relevance
“…Sattar et al , whose results are recorded in Table 2, have found higher reductions of HCoV 229E viral titers with concentrations of hypochlorite greater than the one tested here. These results are then consistent with a concentration-dependent effect [133]. …”
Section: Antisepsis-disinfection: An Efficient Weapon With Room Fsupporting
confidence: 82%
“…Sattar et al , whose results are recorded in Table 2, have found higher reductions of HCoV 229E viral titers with concentrations of hypochlorite greater than the one tested here. These results are then consistent with a concentration-dependent effect [133]. …”
Section: Antisepsis-disinfection: An Efficient Weapon With Room Fsupporting
confidence: 82%
“…102 Studies on inactivation of SARS-CoV (previously discussed) and other coronaviruses are inactivated within 1 minute by phenolics (1.3-2.0 log10 reduction) and 70% ethanol (3.2-3.9 log10 reduction). 103 Hypochlorite with a 1:00 dilution, had a 1 minute decrease of <1 log10.…”
Section: Similarities and Differences Between Sars And Mersmentioning
confidence: 97%
“…59,61 A range of hospital disinfectants are active against SARS-CoV and surrogates, and influenza, including alcohol, hypochlorites (bleach), quaternary ammonium compounds, and hydrogen peroxide, although inactivation is time and concentration dependent and will be influenced by other factors such as type of contaminated surface, specific product, and protein load. 28,45,106,107 However, in-vitro disinfectant effectiveness is a poor predictor for the elimination of contamination from surfaces if cleaning/disinfection is inadequate, which is often the case in hospitals. 108,109 Thus, there may be a role for automated room disinfection (ARD) systems, such as hydrogen peroxide vapour and ultraviolet (UV) light, when patients known to be infected with pandemic influenza or coronaviruses are discharged.…”
Section: Implications For Cleaning and Disinfection And Infection Prmentioning
confidence: 99%